2021
DOI: 10.3390/genes12060909
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Modelling of Gene Expression and Digital Phenotypes to Describe Senescence in Wheat

Abstract: Senescence is the final stage of leaf development and is critical for plants’ fitness as nutrient relocation from leaves to reproductive organs takes place. Although senescence is key in nutrient relocation and yield determination in cereal grain production, there is limited understanding of the genetic and molecular mechanisms that control it in major staple crops such as wheat. Senescence is a highly orchestrated continuum of interacting pathways throughout the lifecycle of a plant. Levels of gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Plants evolve sophisticated genetic programs for determining the appropriate senescence onset and coordinating senescence progression. The onset of senescence is triggered by various endogenous and environmental signals through the coordinated actions of multiple senescence induction pathways ( Woo et al, 2019 ; Camargo Rodriguez, 2021 ). A well-studied genetic pathway for senescence onset in Arabidopsis is the trifurcate death circuit consisting of ORE1, EIN2 as an ORE1 activator, and miRNA164 as an ORE1 repressor.…”
Section: Introductionmentioning
confidence: 99%
“…Plants evolve sophisticated genetic programs for determining the appropriate senescence onset and coordinating senescence progression. The onset of senescence is triggered by various endogenous and environmental signals through the coordinated actions of multiple senescence induction pathways ( Woo et al, 2019 ; Camargo Rodriguez, 2021 ). A well-studied genetic pathway for senescence onset in Arabidopsis is the trifurcate death circuit consisting of ORE1, EIN2 as an ORE1 activator, and miRNA164 as an ORE1 repressor.…”
Section: Introductionmentioning
confidence: 99%
“…Many identified NAC and WRKY TFs have been associated with leaf senescence in Arabidopsis, barley, and wheat [ 15 , 21 , 61 , 62 ]. Over half the NAC genes identified in this study showed a correlation with senescence based on their expression patterns, including NAC21/22 , NAC29 , NAC8 , NAC7 , and three other characterized NAM genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although various factors are interrelated and influence each other, the internal factors play a leading role. Different techniques have been used to identify many senescence-associated genes (SAGs), which are mainly involved in degradation, biosynthetic and regulatory processes, stress responses, and transport [ 13 , 14 , 15 , 16 ]. In SAGs, NAC (no apical meristem (NAM), ATAF1/2, and cup-shaped cotyledon (CUC)) and WRKY transcription factors (TFs) play important roles in regulating gene expression changes during leaf senescence.…”
Section: Introductionmentioning
confidence: 99%